Advancing learning within and beyond the classroom - Lightbody, Bradley (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This insightful book sets out five core elements of good practice that will lead to great teaching and learning both within and beyond the classroom. It looks in detail at the learning process and how teachers can support this through a rich mix of teacher-led direct instruction, collaborative and online learning both flipped and blended. Covering five major themes to reset our pedagogy, Advancing Learning Within and Beyond the Classroom presents the key evidence about 'what works' alongside practical activities to adopt or adapt to enhance your own practice. Chapter cover: the application of precise curricular knowledge the presentation of key questions to guide, check and deepen learning elaboration to build deep understanding feedback to accelerate progress the introduction of regular challenges to drive high learning outcomes and relevant commercial and world-class standards Including a comprehensive overview of evidence-based practice and a wealth of practical strategies to drive engagement and productive learning, this is essential reading for all teachers working in secondary schools or further education"--
Keywords: Effective teaching; High school teaching; College teaching; Experiential learning; EDUCATION / Secondary; EDUCATION / Non-Formal Education; EDUCATION / Distance Education & Learning